Gross Morphometrical Studies on the Testes of Dog During Different Seasons - Gayatri M. Gadariya; Vishnudeo Kumar; Anil Sharma; R. H. Bhatt; R. J. Padodara (Indian Journal of Veterinary Anatomy, 2026)
The present study was conducted on the testes of 18 adult dogs (mean body weight 20.28 ± 0.65 kg) during the summer, monsoon and winter seasons. Thirty-six (36) numbers of testes were collected, 12 in each season, from dogs operated for neutering at the Veterinary Hospital of Municipal Corporation. Gross anatomical and biometrical observations on testicular weight, volume, length, width, thickness and circumference were recorded. The paired testes were located in the scrotum halfway between the anus and the inguinal region. Inside the scrotum, the visceral layer of tunica vaginalis covered the testis and epididymis. The testes had their long axes oriented obliquely with a dorso-caudal direction. The reddish-coloured, roughly oval-shaped testes had two surfaces: lateral and medial, two borders: dorsal and ventral and two ends: proximal and distal. The epididymis was attached dorso-laterally to the testis. The seasonal effect was significant (p<0.05) for all biometrical parameters. Significantly lower (p<0.001) values were recorded during the summer season, while during the monsoon and winter seasons, the values were at par. The lower significant values of testicular biometrical parameters could be correlated with the inactive spermatogenesis in the seminiferous tubules of testis during the summer season.